Olive Oil, Medicinal and Aromatic Plants, and Tomatoes in North-West Tunisia : A Roadmap to Developing Competitive Advantage on Strategic Markets - Salhab, Jade; Weber, Michael; Paganini, Tindaro; Khamassi, Faten; Bellagha, Sihem; Hadj, Houssem Bel; Laabidi, Fatma (World Bank, Washington, DC, 2020)
This report identifies some of the most binding constraints preventing products in targeted value chains in Tunisia from reaching strategic (high value added) markets and proposes a road map on how to strengthen their competitiveness on these market segments. The analysis is anchored in a strategic segmentation exercise and builds on the outputs of a Value Chain Development training program delivered by the World Bank to the members of Tunisia's "Task Force for Value chain and Cluster Development". The training program's tutors complemented and deepened the analyses started by trainees in the cases of the value chains for olive oil, tomatoes, and rosemary. The report provides an illustration of how such a value chain and cluster development approach can be leveraged to accelerate job creation and reduce inequalities between the leading and the lagging regions of Tunisia.